2007
DOI: 10.1080/02786820701501881
|View full text |Cite
|
Sign up to set email alerts
|

Counterflow Virtual Impactor Based Collection of Small Ice Particles in Mixed-Phase Clouds for the Physico-Chemical Characterization of Tropospheric Ice Nuclei: Sampler Description and First Case Study

Abstract: A ground-based sampling system named Ice-CVI is introduced that is able to extract small ice particles with sizes between 5 and 20 μm out of mixed-phase clouds. The instrument is based on a counterflow virtual impactor (CVI) removing interstitial particles and is supplemented by additional modules that pre-segregate other constituents of mixed-phase clouds. Ice particles of 20 μm and smaller are expected to grow only by water vapor diffusion and there is a negligible probability that they scavenge aerosol part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
138
3
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 101 publications
(153 citation statements)
references
References 50 publications
11
138
3
1
Order By: Relevance
“…This is confirmed by Mertes et al (2007) and Kamphus et al (2010) who found a larger number concentration of larger particles in the ice residuals sampled during CLACE-3 and 6, respectively. As mentioned in Sect 2.3, Schwikowski et al (1995) showed that the concentration of larger particles is higher during a dust event than for a non SDE event.…”
Section: Correlations Of In With Mineral Dustsupporting
confidence: 75%
“…This is confirmed by Mertes et al (2007) and Kamphus et al (2010) who found a larger number concentration of larger particles in the ice residuals sampled during CLACE-3 and 6, respectively. As mentioned in Sect 2.3, Schwikowski et al (1995) showed that the concentration of larger particles is higher during a dust event than for a non SDE event.…”
Section: Correlations Of In With Mineral Dustsupporting
confidence: 75%
“…Mineral dust has been recognized as the most relevant IN in the atmosphere (Kamphus et al, 2010;Mertes et al, 2007;Richardson et al, 2007;Cziczo et al, 2004;DeMott et al, 2003). However, it is unlikely that mineral dust is found in its pure, untreated form after a few hours or days of residence time in the atmosphere.…”
Section: Discussionmentioning
confidence: 99%
“…The exact effect of ice clouds on the Earth's climate is yet not well understood (Forster et al, 2007) and more research is needed to determine the mechanisms of heterogeneous ice nucleation (Cantrell and Heymsfield, 2005). Mineral dust has been found to be one of the major components of snow crystal residuals (Kamphus et al, 2010;Mertes et al, 2007;Richardson et al, 2007;Cziczo et al, 2004;DeMott et al, 2003). In the atmosphere mineral dust is often internally mixed with organic and inorganic material due to particle ageing processes in the atmosphere (Wiacek and Peter, 2009;Hinz et al, 2005;Falkovich et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Several intensive cloud characterization experiments have been conducted there for many years at different times of the year (e.g. Mertes et al, 2007;Verheggen et al, 2007;Cozic et al, 2008;Targino et al, 2009;Kamphus et al, 2010;Zieger et al, 2012). The aerosol measurements performed at the JFJ are part of the Global Atmosphere Watch (GAW) program of the World Meteorological Organization since 1995 (Collaud Coen et al, 2007).…”
Section: Instrumentation and Sitementioning
confidence: 99%